STUDENTS' PERCEPTION OF USING ROLE-PLAY TECHNIQUE IN LEARNING SPEAKING - Laelati Madarina; Sahuddin Sahuddin; Amrullah Amrullah (Program Studi Pendidikan Bahasa Inggris, 2021)
The purpose of this research is to discover the students' perceptions of utilizing the role-play technique in learning to speak and to determine whether the role-play technique is acceptable for students' speaking skill development. There were 34 students from the eleventh-grade students at SMAN 1 Bolo Bima participated in this research. The data were gathered through a questionnaire, interview, and performance on a speaking exam. Based on the findings, the students' opinions of employing the role-play technique can be categorized positive. Meanwhile, the students' performance on the speaking test improved by 55.88 percent from pre-test to post-test. In conclusion, the role-playing technique is appropriate for the development of students' speaking skills.